Perceptions of Health Workers regarding the COVID-19 Vaccine Report Application in Ogan Ilir Regency, South Sumatra - Idris, Haerawati; Rosyada, Amrina; Budiastuti, Anggun; Ermi, Nurmalia (UI Scholars Hub, 2023)
The Lapor Vaksin COVID-19 Application was developed to support a vaccination coverage surveillance database sourced from community self-report. This application provides data on vaccination coverage and allows users to view updates to educational content about vaccines and visualization of COVID-19 vaccine data in real-time. This study aims to analyze the perception among health worker about Lapor Vaksin COVID-19 application in the community. This study uses descriptive research with a case study design. This study was conducted in September 2021 through a virtual zoom meeting, in Ogan Ilir Regency, South Sumatra. The research sample was 42 health workers consisting of vaccine officers at the Health Office, RSUD and Puskesmas in Ogan Ilir Regency who were selected by purposive sampling. Data is presented descriptively. Based on the evaluation results of the application's use, more than half of the respondents were quite satisfied (52.4%) with the Lapor Vaksin COVID-19 application. This application can be used and developed as an alternative to the COVID-19 surveillance database.